Análise de viabilidade da coleta seletiva na cidade de Valparaíso - SP - Antoniali, Natalia [UNESP] (2013)
Before starting any project of selective collection and recycling of solid waste, it is important to characterize the quality of the quantity and types of waste generated. This characterization allows better structuring a project appropriate selective collection, and this is a key point to the return of the material to a new production process through recycling or reuse. The objective of this research was to conduct economic viability analysis of selective collection in the city of Valparaíso - SP, for this, it was necessary to characterize by identifying recyclable solid waste with higher added value generated in the city and quantify residues generated the urban population. With these results it can be inferred that the selective collection in the city of Valparaiso is viable considering the Benefit - Cost Ratio (CBR) calculated same to 2.805, ie CBR > 1, however, the market values must be updated periodically